Pharmacogenetics as a Way for Personalizing Diuretic Therapy: Focus on Torasemide - N. M. Gafurova; E. V. Shikh; O. D. Ostroumova (Рациональная фармакотерапия в кардиологии)
Optimizing diuretic therapy in patients with chronic heart failure is a complicated problem with many unresolved questions. Diuretics take an important place in the treatment of heart failure, which are used in almost 80% of cases. Currently, there are not enough clinical studies, which comparative effectiveness of loop diuretics, as well as studies aimed at personalizing diuretic therapy. Torasemide has several advantages over other loop diuretics; high bioavailability, longer half-life and duration of action provide predictable diuresis. The presence of favorable neurohormonal effects, consisting in a decrease of sympathetic activity and inhibition of the renin-angiotensin-aldosterone system, leads to the fact that hypokalemia rarely occurs. In addition, torasemide slows development of myocardial fibrosis and fosters reverse ventricular remodelling. The use of personalization methods is one of the ways to increase the efficiency and safety of pharmacotherapy with diuretics. The polymorphism of genes encoding systems of biotransformation and transporters of drug is an important factor that determines the individual characteristics of a patient. Pharmacogenetics of torasemide may be of significant importance for pharmacokinetics and pharmacodynamics, influencing the intensity of the diuretic effect and side effects. The clearance of torasemide after oral administration may vary by 47% due to genetic characteristics: the participation of the OATP1B1 polymorphism is approximately 15.5%, the CYP2C9 polymorphism is 20%, and the OAT1 and OAT4 polymorphisms are 10%. Due to the significant differences in the pharmacokinetics of torasemide, further study of the pharmacodynamic characteristics of torasemide in patients with genetic polymorphism is necessary.